Cephalalgia: A Case Report Highlighting Holistic Management and Preventive Strategies in Primary Care - Wulan Suci Lestari (Universitas Pahlawan Tuanku Tambusai, 2026)
Cephalgia, or headache, is one of the most common medical problems worldwide. It greatly affects daily life and overall well-being. This report describes a 48-year-old female farmer who visited a community health center. She had a three-day history of recurrent, throbbing headaches, along with nausea. The headaches were characterized by widespread, pulsating pain that lasted about six hours per episode. Physical activity made the pain worse. A normal neurological exam led to a diagnosis of migraine without aura. The case analysis identifies several contributing factors. These include irregular sleep patterns, dietary habits (especially coffee consumption), occupational stress, and environmental triggers such as heat and possible noise. Management involved various approaches. This included using medications, specifically paracetamol and domperidone, as well as non-drug strategies such as rest, cold compresses, and stress management. There was also a strong focus on educating the patient about avoiding triggers and making lifestyle changes. Additionally, a prevention model was outlined in three tiers. The first tier focused on lifestyle education. The second tier involved identifying triggers and providing preventive measures. The third tier addressed rehabilitation and the prevention of complications. This case emphasizes the complex nature of migraines. It also underscores the importance of a comprehensive, patient-centered management plan that integrates medical treatment with health promotion and prevention in primary care.